IMPLEMENTASI PSAK 65 PADA LAPORAN KEUANGAN KONSOLIDASI PT. TELKOM INDONESIA TBK DAN ENTITAS ANAK - Rohma, Miptaqul; Afendi, Dyana (JUMBA (Jurnal Manajemen, Bisnis, dan Akuntansi), 2023)
It was found that PT. Telkom Indonesia Tbk. has applied PSAK 65 in its consolidated financial statements evidenced in the contingent consideration classified as equity or financial liabilities. Amounts classified as financial liabilities are subsequently remeasured at fair value where changes in fair value are recognized in profit or loss or when adjustments are recorded outside the measurement period. Changes in the fair value of the contingent consideration that qualify as measurement period adjustments are adjusted retrospectively, with the related adjustments to goodwill. As of March 31, 2021 and December 31, 2020, the carrying values of the Group's trade receivables that were past due but not impaired were Rp.4,657 billion and Rp.4,217 billion, respectively. Measurement period adjustments are adjustments arising from additional information obtained during the measurement period, which may not exceed one year from the acquisition date, about facts and conditions that existed at the acquisition date.